Potret Berbagai Problematika Pembelajaran Bahasa Jawa di SMA Wilayah Provinsi Jawa Tengah - Astiana Ajeng Rahadini; Nirbito Hanggoro Pribadi (Fakultas Bahasa Seni dan Budaya, 2025)
Learning problems greatly influence the achievement of learning objectives. Teachers need to know what problems occur in the classroom so they can formulate possible solutions so that learning can achieve the goals set in the curriculum. This research aims to identify any problems that occur in learning Javanese. The method used in this research is a qualitative method. Data was obtained by surveys and interviews. Surveys and interviews were conducted with Javanese language teachers and students spread across high schools in Central Java. Data analysis was carried out by grouping problematic points in Javanese language learning experienced by teachers and students. The research results show that the problems of learning Javanese lie in the problems of teachers, students, teaching materials, learning methods, learning media, and infrastructure. All these problems mean that the goals of learning Javanese have not been achieved optimally. The results of this research can be input for stakeholders conducting curriculum evaluation.